Dynamics of Motivational Levers Influenced by the Pandemic - Vonberg Tetyana V. (PH "INZHEK", 2021)
The article is aimed at analyzing the motivational levers for effective work, which used to be effective before the beginning of the COVID-19 pandemic and became effective after it. The article substantiates the relevance of studying motivational factors and probable changes in the motivational components of employees that arose in response to the emergence of a new virus and the necessity to profoundly change the usual activity schemes. Having analyzed and summarized the research in the field of motivation and incentives to work effectively, the authors have found out that the issue of changing motivational levers during the pandemic remains greatly unsolved, despite numerous developments. The study makes it possible to draw certain conclusions, namely: the pandemic has clearly affected the employees’ motivation and productivity, but this effect remains rather insignificant. For example, with the beginning of the pandemic, the share of respondents experiencing an average level of satisfaction with their work decreased, while the share of both respondents experiencing the highest level of satisfaction and those who were dissatisfied with their work, increased. Also, with the onset of the pandemic, the share of productive respondents decreased, while the share of respondents showing high and low levels of productivity increased. The study shows that with the onset of a pandemic, stability, comfortable workplace conditions and the prospect of additional income have become more important; at the same time, such factors as competitive wages and career opportunities have gradually begun to lose their leadership in the list of important motivational components for productive work. The survey confirms that over the past year, employees have increasingly begun to value stability and socially responsible attitude demonstrated by employers; and more and more employees have begun to appreciate a company’s attitude to its personnel during the heyday of the pandemic, its willingness to change along with changes in the environment, its readiness to support its personnel and suggest help if need be.